Kinematic determinants of dive height in springboard diving - Sinclair, P. J.; Walker, C. A.; Rickards, T. (Science et motricité, 2012)
The aim of the present investigation was to identify the kinematic characteristics of dives that produce a greater peak flight height. Eight junior divers (13.25 ± 1.04 years) performed forward somersault dives at three different fulcrum settings off a one metre springboard. Selected variables were input to a stepwise regression analysis to identify predictors of dive height. Significant predictor variables were vertical velocity at touchdown, angle of lean at takeoff, vertical displacement at touchdown, ankle angle at touchdown, and external work. External work done during takeoff, although a significant predictor of dive height, was of relatively minor influence when compared to the kinematic variables. This study emphasises the importance of the hurdle flight in setting touchdown parameters that strongly determine take-off characteristics.